2011
DOI: 10.1017/s0033291710002540
|View full text |Cite
|
Sign up to set email alerts
|

Access of emotional information to visual awareness in patients with major depressive disorder

Abstract: Our finding of preferential access to awareness for mood-congruent stimuli supports the notion that depressive perception may be related to altered sensory information processing even at automatic processing stages. Such perceptual biases towards mood-congruent information may reinforce depressed mood and contribute to negative cognitive biases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
70
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 51 publications
5
70
1
Order By: Relevance
“…These studies consistently showed an increased accuracy of, and increased response bias for sad faces (Arteche et al, 2011;Gollan et al, 2010Gollan et al, , 2008Gur et al, 1992;Hale, 1998;Lee et al, 2008;Mandal and Bhattacharya, 1985;Sterzer et al, 2011;Surguladze et al, 2004). These emotionalcognitive deficits seem to persist during remission (Bhagwagar and Cowen, 2008;Bouhuys et al, 1999;Fuhr et al, 2014;Joormann and Gotlib, 2007;Lange et al, 2012).…”
Section: Introductionmentioning
confidence: 79%
“…These studies consistently showed an increased accuracy of, and increased response bias for sad faces (Arteche et al, 2011;Gollan et al, 2010Gollan et al, , 2008Gur et al, 1992;Hale, 1998;Lee et al, 2008;Mandal and Bhattacharya, 1985;Sterzer et al, 2011;Surguladze et al, 2004). These emotionalcognitive deficits seem to persist during remission (Bhagwagar and Cowen, 2008;Bouhuys et al, 1999;Fuhr et al, 2014;Joormann and Gotlib, 2007;Lange et al, 2012).…”
Section: Introductionmentioning
confidence: 79%
“…In Experiments 6, 7, and 9, we used the binomial distribution to determine whether each participant performed better than chance on the objective block and excluded from analyses all those participants who did (21,30, and 7 participants in Experiments 6, 7, and 9, respectively). Note that, although the number of excluded participants may seem high, they fall within the normal range of long-duration CFS priming, in which successful suppression is strongly affected by individual differences (38). We additionally excluded participants who reported any subjective awareness of the primes (four, five, and three participants in Experiments 6, 7, and 9, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it was shown that states of pleasant affect lead to a dominant perception of smiling faces, whereas unpleasant affect leads to a dominant perception of scowling faces (Anderson, Siegel, & Feldmann Barrett, 2011). Trait anxiety was also shown to influence the initial selection of emotional faces (Gray, Adams, & Garner, 2009) and a recent study could demonstrate (with a variant of binocular rivalry) that mood-congruent stimuli such as sad faces gain preferential access to awareness in depressive patients (Sterzer, Hilgenfeldt, Freudenberg, Bermpohl, & Adli, 2011). …”
Section: Introductionmentioning
confidence: 99%